Spark for Python developers : a concise guide to implementing Spark big data analytics for Python developers and building a real-time and insightful trend tracker data-intensive app /: a concise guide to implementing Spark big data analytics for Python developers and building a real-time and insightful trend tracker data-intensive app. (2015) - Nandi, Amit
No abstract available